2018
DOI: 10.1080/21645515.2018.1428507
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of pneumococcal vaccines for adults aged over 50 years in Belgium

Abstract: Streptococcus pneumoniae causes a high disease burden including pneumonia, meningitis and septicemia. Both a polysaccharide vaccine targeting 23 serotypes (PPV23) and a 13-valent conjugate vaccine (PCV13) are indicated for persons aged over 50 years. We developed and parameterized a static multi-cohort model to estimate the incremental cost-effectiveness and budget-impact of these vaccines at different uptake levels. Using three different vaccine efficacy scenarios regarding non-invasive pneumococcal pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Compared with the low-risk group, the high-risk group could avoid more death and cases, vaccinating with PPSV-23 is more cost-effectiveness. Studies from UK ( 8 ), Japan ( 27 ), and Belgium ( 28 ) have also demonstrated that vaccination with PPSV-23 was a cost-effective intervention for preventing pneumococcal diseases. However, Chen et al ( 29 ) suggest that compared with people who are not vaccinated, vaccination with PPSV-23 is not economical.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the low-risk group, the high-risk group could avoid more death and cases, vaccinating with PPSV-23 is more cost-effectiveness. Studies from UK ( 8 ), Japan ( 27 ), and Belgium ( 28 ) have also demonstrated that vaccination with PPSV-23 was a cost-effective intervention for preventing pneumococcal diseases. However, Chen et al ( 29 ) suggest that compared with people who are not vaccinated, vaccination with PPSV-23 is not economical.…”
Section: Discussionmentioning
confidence: 99%
“…Recent European cost-effectiveness studies of PCV13 vaccination in the adult population that used effectiveness data from the CAPiTA study present considerable variability in results. [39][40][41][42][43][44][45][46][47] The heterogeneity of the results in published literature might be explained by differences in the comparators (PPSV23 or no vaccination), target age for vaccination, assumptions regarding resource use and costs, approaches followed to include the indirect effect of childhood vaccination in the models, dynamics of vaccination serotype coverage over time, calibration of the PPSV23 effectiveness and the incidence rate of IPD in adult population, in particular of hospitalized pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that vaccines against influenza [44,45], pneumococcus [46][47][48][49] and herpes zoster [50][51][52] are cost-effective when given to older adults in a range of settings [53]. Notwithstanding this, the corresponding global economic burden offset by these adult VPD vaccines has not been fully calculated.…”
Section: Economic Benefits Of Older Adult Immunizationmentioning
confidence: 99%